“A Comparative Study of Perception towards Artificial Intelligence and Sustainable Development among Urban and Rural College Students.” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The current research was conducted to analyse the attitude of College students towards Artificial Intelligence (AI) and Sustainable Development and also to compare the perspective of urban and rural students as well as male and female students. Artificial Intelligence has emerged as a game changer technology affecting a variety of industries such as education, health, agriculture, environment management and government. At the same time sustainable development has become a worldwide goal for the balanced economic growth, environmental conservation and social well-being. A descriptive survey approach with a comparative research design was used in the study. A sample of 100 undergraduate college students including 50 urban and 50 rural students equally distributed between male and female students was recruited using stratified random selection from selected institutions of West Bengal. To gather data, the researcher prepared a self-structured instrument named as “Perception Scale on Artificial Intelligence and Sustainable Development” (PSAISD).Data were analysed using statistical procedures including Mean, Standard Deviation and t - test. The results indicated that urban students had considerably more awareness levels towards AI and Sustainable Development than rural students owing to more exposure to technology and internet accessibility. The perception ratings of female students were marginally higher than those of male students with no statistically significant differences. The report also pointed to students’ understanding of AI applications in education, healthcare and environmental sustainability, and their worries around ethics, privacy and jobs. The report highlights the need of inclusive AI education, better digital infrastructure and awareness campaigns to encourage sustainable tech behaviours among students.